SCM Professionals’ Competences in Brazil - Reis, Manoel A. S.; Minerbo, Claudio; Miguel, Priscila L. S. (Brazilian Journal of Operations & Production Management, 2021)
Goal: This paper aims to examine the competences required from supply chain management professionals in Brazil. Design / Methodology / Approach: A survey with 239 professionals explored 44 different competences they deemed important. Results: Competences can be grouped in eight categories, some of which updated to reflect the changes in the SCM practice. It reinforces the importance for general behavioral, technical, analytical and business competences, suggested in previous research, and provides a more granular view and emphasizes differences of technical expertise depending on the scope of the manager's function. Technology, information systems and quantitative skills are different competences required to support changes in e-commerce and digital transformations. Limitations of the investigation: Differences among industry sectors or functions should be investigated in more detail due to respondent´s heterogeneity Practical implications: Our study can serve as a guide when searching new talents and training SCM professionals, as it emphasizes competences common to all SCM functions and specific depending on their scope. Originality / Value: Firms operating in service sectors generally demand higher levels of business awareness competences than the ones in manufacturing sectors. This reflects the service-dominance logic, where service is the fundamental basis of exchange and firms need to be more customer oriented.